2016
DOI: 10.3897/jhr.51.9727
|View full text |Cite
|
Sign up to set email alerts
|

Host-associated volatiles attract parasitoids of a native solitary bee, Osmia lignaria Say (Hymenoptera, Megachilidae)

Abstract: Parasitoids use volatiles to recognize and locate suitable hosts. Numerous studies have investigated parasitoid host location from a pest management perspective, but comparatively little is known regarding parasitoid-pollinator interactions. Previous research has shown that parasitoids of some native bees respond to volatiles emitted by host frass and cocoons. We used a Y-tube bioassay to test whether two parasitoid species (Monodontomerus torchioi and Melittobia acasta) are attracted to volatiles associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Studies such as these are still scarce, but no less relevant, since in identifying VOCs, they can be applied in bioassays. The study conducted by Glasser and Farzan (2016) with the bee species Osmia lignaria (Megachilidae) showed that two species of parasitoids are attracted by VOCs present in the nests of this bee. The possibility of this occurring also in other specific beeparasitoid relationships has to be investigated, since it allows to use baits for the attraction of parasitoids avoiding the infestation of the nests of the bees, which would lead to a decrease in their population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies such as these are still scarce, but no less relevant, since in identifying VOCs, they can be applied in bioassays. The study conducted by Glasser and Farzan (2016) with the bee species Osmia lignaria (Megachilidae) showed that two species of parasitoids are attracted by VOCs present in the nests of this bee. The possibility of this occurring also in other specific beeparasitoid relationships has to be investigated, since it allows to use baits for the attraction of parasitoids avoiding the infestation of the nests of the bees, which would lead to a decrease in their population.…”
Section: Discussionmentioning
confidence: 99%
“…Volatile compounds would also be involved in the recognition of the nest by solitary bees that nest in clusters (Wcislo, 1992). In addition, they would facilitate the location of nests by parasitoids, as observed in nests of Osmia lignaria (Megachilidae) (Glasser & Farzan, 2016). In this sense, the chemical ecology has proven important because it allows the recognition and identification of the volatile organic compounds (VOCs) involved in the attraction to nests that were already used, recognition of nests and parasitism.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we show that macropterous females of Melittobia species clearly rely on semiochemical exploitation of host-associated cues when searching for hosts. Volatiles released by cocoons enveloping the host prepupae thus are not only relevant for M. digitata and M. acasta (Silva-Torres et al, 2005a;Cusumano et al, 2010;Glasser and Farzan, 2016), but these host semiochemicals appear to mediate the host finding behavior in several species within the genus Melittobia. Interestingly, different Melittobia species displayed variation in terms of behavioral response toward odors emitted by leafcutter bees, mud dauber wasps, honeybees and flesh flies.…”
Section: Discussionmentioning
confidence: 99%
“…The ancestral host of Melittobia species is not known but it is possible that some solitary cavity-nesting bees which nested in aggregated situations are closely related to the original natural hosts, from which the host range could have been expanded to include solitary wasps such as mud dauber wasps which are notable because females tend to build nests in clusters (Malyshev, 1968;Cross et al, 1975;Molumby, 1995). Up-to date, only the host location process of 2 species of the acasta species-group (M. digitata and M. acasta) has been investigated showing that long-winged females are attracted by volatile semiochemicals emitted by the cocoons of mud dauber wasps (Cusumano et al, 2010) and megachilid leaf-cutting bees (Silva-Torres et al, 2005a,b;Glasser and Farzan, 2016) which envelop the host prepupa, i.e., the host stage attacked. However, it is not known whether the other Melittobia species have evolved a similar host location strategy based on exploitation of hostassociated chemical cues.…”
Section: Introductionmentioning
confidence: 99%
“…For example, two parasitoids from their native range, Chaetodactylus spp. and Melittobia acasta have been documented in O. cornifrons and O. lignaria , respectively, but not in O. taurus in North America (McKinney and Park 2013, Glasser and Farzan 2016). Other parasites and pathogens such as Vairimorpha spp.…”
Section: Nesting Biology Life Cycle Floral Preferences and Natural En...mentioning
confidence: 99%